EEG BIOFEEDBACK THERAPY FOR ADHD: A SYSTEMATIC REVIEW. Issue 8 (9th July 2014) - Liew, Ashley
Abstract : Objective: To examine systematically the evidence for the application of electroencephalographic (EEG) biofeedback, otherwise called neurofeedback, in the treatment of children and young people with Attention Deficit Hyperactivity Disorder (ADHD). Method: A literature search of 8 electronic databases was conducted to identify articles published between February 1985 and February 2013. Furthermore, researchers in the field and professional organisations were contacted for access to unpublished data. The review was restricted to intervention studies, although they did not have to be randomised controlled trials. For each study, the quality of the methods and the strength of the evidence were assessed using the evidence based guidelines devised by Sackett. Results: A total of 112 studies were identified, of which 26 met the inclusion criteria. As some of these included follow-up data, a total of 20 separate studies were identified. 8 studies were randomised controlled trials. All the studies demonstrated significant improvements for neurofeedback across a range of cognitive and behavioural measures. However, several important weaknesses were identified in the methodology of the majority of the studies, namely, absence of blinding, lack of randomisation and small sample sizes. More recent studies have overcome some of these weaknesses through novel designs, but important limitations remain. Conclusion: There is growing evidence for neurofeedback as a non-pharmacological alternative in the treatment of ADHD, but the existing literature displays a range of methodological weaknesses. Further and more convincing research is required.